Studies in Soviet Thought
150 p.
Keywords: Early in 1958 a number of research projects on Soviet philosophy were started at the Institute of East-European Studies at the University of Fribourg (Switzerland) under the direction of the undersigned. At present, they are all completed or nearly so and their results are described in 18 different volumes. In spite of the fact that all of them have been already published or soon will be (mostly in German), it has been thought worthwhile to present their main conclusions in the form of short English reports. This book contains in the main these reports. Only the two programmatic papers (my own and that of Dr. Buchholz) and the study of Dr. Dahm are not direct results of the above-mentioned projects. But it will be clear to everyone that they, too, are closely connected with the subject envisaged and are written from a similar point of view. It will, perhaps, be convenient to briefly formulate this standpoint. All the writings included here are concerned with recent (i. e. mainly post Stalinist) developments in Soviet philosophy, where "Soviet" is taken in the wide meaning of the word, covering also Marxism-Leninism in Communist countries other than the Soviet Union. All the authors started with the assumption that there are interesting aspects to these more recent developments. There was also a common assumption that only specialized work on first-hand sources can be of relevance in this field.